(untitled) (Journal of Science and Technology, 2016)
Numerical models of unsteady flow in irrigation canals are commonly used to predict the arrival time and the arrival flow rate of water at a turnout. To evaluate the performance of such numerical models, the data obtained from numerical simulation are converted into appropriate indices. The mass conversation index, the wavelength ratio index, the wavelength ratio index, and the mass distribution index are proposed for the above-mentioned purpose. These indices could enhance the selection of appropriate numerical models, which predict the arrival time and the arrival flow rate more accurately. Gate operators can thus operate systems close enough to the intended flow pattern. This provision will improve water deliveries to farmers.